Reconciling Technophilia and Technophobia Using Intrarole Identity Tensions: A Paradox Theory Perspective - Shahmehr, Fatemeh S.; Khaksar, Seyed Mohammad Sadegh; Miah, Shah J.; Moughari, Mahdieh Mokhtari; Daim, Tugrul (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
The application of social service robots in organizational contexts may be perceived negatively or positively, shaping varying forms of intrarole identities. Positive perceptions and attitudes are mostly referred to the concept of technophilia, a strong enthusiasm for new technologies. In contrast, negative perceptions are explained by the concept of technophobia, the fear or aversion to technology. There is a limited understanding of how both technophilia and technophobia traits can together cause paradoxical tensions in a role, making opposing sides of the role salient. In this article, we aim to unpack the theoretical grounds of technophilia and technophobia traits by identifying intrarole paradoxical tensions. Identifying these tensions can offer a well-adjusted explanation of how contradictions within a role evolve and persist in times of using technologies. We applied a grounded theory methodology to generating and conceptualizing data to eventually help the emergence of concepts that shape the technophilia-technophobia spectrum. We identified and conceptualized three intrarole identity paradoxical tensions: caring identity-controlling identity; technology leadership identity-technology followership identity; and autonomous identity-coercive identity. These paradoxical tensions reveal why employees uphold both technophilia-technophobia traits simultaneously when using social service robots. We also articulated the coping strategies that employees maintain to strike a balance between opposing identities.
Keywords: Service robots; Medical services; Aging; Older adults; Focusing; Engineering management; Australia; Human-robot interaction; intrarole identity; paradox theory; technophilia; technophobia; tension; GROUNDED THEORY; TECHNOLOGY; ACCEPTANCE; CARE; MANAGEMENT; CONFLICT; ADOPTION; FUTURE; MODEL; ROBOT; Business & Economics; Engineering